Lubrication effects on the flow of wet granular materials - Xu, Qing; Orpe, Ashish V.; Kudrolli, Arshad (Physical Review E, 2007)
We investigate the dynamics of a partially saturated grain-liquid mixture with a rotating drum apparatus. The drum is partially filled with the mixture and then rotated about its horizontal axis. We focus on the continuous avalanching regime and measure the impact of the volume fraction and viscosity of the liquid on the dynamic surface angle. The inclination angle of the surface is observed to increase sharply to a peak and then decrease as a function of liquid volume fraction. The height of the peak is observed to increase with rotation rate. For higher liquid volume fractions, the inclination angle of the surface can decrease with viscosity before increasing. The viscosity where the minimum occurs decreases with the rotation rate of the drum. Limited measurements of the flow depth were made, and these were observed to show only fractional changes with volume fraction and rotation speeds. We show that the qualitative features of our observations can be understood by analyzing the effect of lubrication forces on the time scale over which particles come in contact.

Velocity correlations in dense granular flows observed with internal imaging - Orpe, Ashish V.; Kudrolli, Arshad (Physical Review Letters, 2007)
We show that the velocity correlations in uniform dense granular flows inside a silo are similar to the hydrodynamic response of an elastic hard-sphere liquid. The measurements are made using a fluorescent refractive-index-matched interstitial fluid in a regime where the flow is dominated by grains in enduring contact and fluctuations scale with the distance traveled, independent of flow rate. The velocity autocorrelation function of the grains in the bulk shows a negative correlation at short time and slow oscillatory decay to zero similar to simple liquids. Weak spatial velocity correlations are observed over several grain diameters. The mean square displacements show an inflection point indicative of caging dynamics. The observed correlations are qualitatively different at the boundaries.

Erosion of a granular bed driven by laminar fluid flow - Lobkovsky Alexander E.; Orpe, Ashish V.; Molloy, Ryan; Kudrolli, Arshad; Rothman, D. H. (Journal of Fluid Mechanics, 2008)
Motivated by examples of erosive incision of channels in sand, we investigate the motion of individual grains in a granular bed driven by a laminar fluid to give us new insights into the relationship between hydrodynamic stress and surface granular flow. A closed cell of rectangular cross-section is partially filled with glass beads and a constant fluid flux Q flows through the cell. The refractive indices of the fluid and the glass beads are matched and the cell is illuminated with a laser sheet, allowing us to image individual beads. The bed erodes to a rest height hr which depends on Q. The Shields threshold criterion assumes that the non-dimensional ratio θ of the viscous stress on the bed to the hydrostatic pressure difference across a grain is sufficient to predict the granular flux. Furthermore, the Shields criterion states that the granular flux is non-zero only for θ > θc. We find that the Shields criterion describes the observed relationship hr ∝ Q1/2 when the bed height is offset by approximately half a grain diameter. Introducing this offset in the estimation of θ yields a collapse of the measured Einstein number q* to a power-law function of θ − θc with exponent 1.75 ± 0.25. The dynamics of the bed height relaxation are described well by the power-law relationship between the granular flux and the bed stress.

Fast decay of the velocity autocorrelation function in dense shear flow of inelastic hard spheres - Orpe, Ashish V.; Kumaran, V.; Reddy, K. Anki; Kudrolli, Arshad (EPL, 2008)
We find in complementary experiments and event-driven simulations of sheared inelastic hard spheres that the velocity autocorrelation function psi(t) decays much faster than t(-3/2) obtained for a fluid of elastic spheres at equilibrium. Particle displacements are measured in experiments inside a gravity-driven flow sheared by a rough wall. The average packing fraction obtained in the experiments is 0.59, and the packing fraction in the simulations is varied between 0.5 and 0.59. The motion is observed to be diffusive over long times except in experiments where there is layering of particles parallel to boundaries, and diffusion is inhibited between layers. Regardless, a rapid decay of psi(t) is observed, indicating that this is a feature of the sheared dissipative fluid, and is independent of the details of the relative particle arrangements. An important implication of our study is that the non-analytic contribution to the shear stress may not be present in a sheared inelastic fluid, leading to a wider range of applicability of kinetic theory approaches to dense granular matter. Copyright (C) EPLA, 2008

Physical test of a particle simulation model in a sheared granular system - Rycroft, Chris H.; Orpe, Ashish V.; Kudrolli, Arshad (Physical Review E, 2009)
We report a detailed comparison of a slow gravity-driven sheared granular flow with a discrete-element simulation performed in the same geometry. In the experiments, grains flow inside a silo with a rectangular cross section and are sheared by a rough boundary on one side and smooth boundaries on the other sides. Individual grain position and motion are measured using a particle index-matching imaging technique where a fluorescent dye is added to the interstitial liquid which has the same refractive index as the glass beads. The simulations use a Cundall-Strack contact model between the grains using contact parameters that have been used in many other previous studies and ignore the hydrodynamic effects of the interstitial liquid. Computations are performed to understand the effect of particle coefficient of friction, elasticity, contact model, and polydispersity on mean flow properties. We then perform a detailed comparison of the particle fluctuation properties as measured by the displacement probability distribution function and the mean square displacement. All in all, our study suggests a high level of quantitative agreement between the simulations and experiments.